Art/Archaeology: What Value Artistic- Archaeological Collaboration? - Bailey, Doug (Journal of Contemporary Archaeology, 2018)
Recent work by artists and archaeologists has explored the potential for collaboration between the two disciplines. While much aesthetically pleasing and intellectually stimulating work has emerged, most output remains limited in its extramural impact. This short note argues for a more robust practice though an art/archaeology, a practice that goes beyond the limits of the archaeological study of prehistoric, ancient or historic art, but engages modern and contemporary political and social action. At the core of an art/archaeology are three successive processes: disarticulation, repurposing, and disruption. The article works through the example of an anthropomorphic figurine and a ceramic vessel, and it concludes with a call for a more-applied output.